The antecedents of word of mouth intentions about a Brazilian tourist destination - Márcio Moutinho Abdalla; José Roberto Ribas; Paulo Roberto da Costa Vieira (Tourism & Management Studies)
The purpose of this research is to assess the constructs positive affection, negative affection, service quality, hedonic value, utilitarian value and satisfaction as antecedents considered by foreign tourists in their intention to recommend a Brazilian tourist destination. The analysis was supported by structural equation modeling of a crosssectional sample of 203 foreign tourists. Data were collected through a structured questionnaire of 22 questions, adapted from the study by Babin, Lee, Kim & Griffin (2005). Regarding the objective of this study, the results suggest that only the latent variables satisfaction and hedonic value are directly related to the intention to recommend a Brazilian tourist destination by foreign tourists. Furthermore, the analysis confirms that tourist satisfaction positively influences intention to recommend the destination, which is consistent with the hypothesis signalized by previous studies.